Compulsory Vaccinations against Covid-19 versus the Right to Respect for Private Life - Miaskowska-Daszkiewicz, Katarzyna (Medicine, Law & Society, 2021)
The development and marketing authorisation of COVID-19 vaccines has given the authorities a much-anticipated instrument to fight a pandemic. At the same time, however, for the extinction of the epidemic to become real, according to epidemiologists’ estimates, the threshold of herd immunity must reach the value of 50-70 percent. To ensure mass vaccination, it should be considered whether a compulsory vaccination against COVID-19 would be an acceptable solution. It is a sensitive issue in the context of the right to self-determination, guaranteed both in Article 8 European Convention on Human Rights, as well as most modern constitutions. The aim of this paper is to investigate whether the compulsory vaccination against COVID-19 could be the next step in the fight against the pandemic. In particular, whether the current approach of the ECHR and national courts to compulsory vaccination can be considered adequate in relation to COVID-19 vaccines with a conditional marketing authorisation.